Financial sustainability of modern composting: the economically optimal scale for municipal waste composting plant in developing Asia - Andante Hadi Pandyaswargo; Dickella Gamaralalage Jagath Premakumara (International Journal of Recycling of Organic Waste in Agriculture)
There is a widespread interest in converting organic waste into compost fertilizer to extend the life of landfills, create economic and environmental benefits, and ultimately reduce the pressure on local governments in managing the ever-increasing complexity of municipal solid waste. However, composting is still seldom considered as a strategic element. There is also very little evidence available of its economic feasibility. This study, therefore, aims to analyze key factors that influence the economic feasibility of municipal composting plant and identify a range of plant capacity or scale where a composting project could have higher opportunity to be financially sustainable. A costâbenefit analysis (CBA) was carried out using the data gathered from five composting plants in Asia, including Surabaya, Bali and Bekasi in Indonesia, Beijing in China, and Matale in Sri Lanka. The results identified that the medium-scale and lower largescale composting plants have an optimal opportunity for being financially feasible as compared with the smaller and larger capacity plants. The study also identified that the economic viability of the composting plants depends on the number of factors, such as selection of suitable processing methods, technologies, scale, quality of product and marketing strategies. The advantages of the medium and lower large-scale composting plants are (1) waste input and product quality are easier to control than larger scale compost plants, and (2) there are extra income opportunities such as tipping fees and carbon credits that are limited in the case of small-scale composting plants. The scale of composting plant is one of the key factors to be considered at the initial stage of planning composting plants.